Globalization and Iranian identity (relying on the ideas of Dariush Shayegan) - fazeli, habib ollah; Nazari , Meysam (Advances in Social Sciences Research Journal, 2019)
Abstract Dariush Shayegan, as one of the most prominent Iranian scholars in the last five decades, is known as “cultural theorist” due to the cultural nature of his philosophical thoughts. The influence of his theories about identity and cultural confrontations, between traditional civilizations and modernity is global and has associated his name with the idea of “dialogue of civilizations”. Shayegan’s works could be divided to, and examined within, two categories of the early and the later Shayegan. To discuss his thoughts and ideas about identity, the early Shayegan relies on the East/West dialogue and puts emphasis on the genuine identities of traditional civilizations confronting modernity and the Western civilization. However, through taking a different and critical approach, the later Shayegan examines the concept of identity in traditional societies as well as the multilayered and bricolage identity of the modern humankind. The present paper is to discuss the later Shayegan’s critiques on the notion of search for vernacular identity as well as his definition of the relationship between identity and the phenomenon of globalization. From a theoretical perspective, the paper relies on Shayegan’s support of the multiple-layered identity of the modern human and his reject of blind search for identity in a globalized world. Moreover, the paper addresses the idea of bricolage identity that encompasses the epistemic efforts of the later Shayegan.